2011
DOI: 10.3138/cpp.37.3.359
|View full text |Cite
|
Sign up to set email alerts
|

Attributing Selected Costs to Intimate Partner Violence in a Sample of Women Who Have Left Abusive Partners: A Social Determinants of Health Approach

Abstract: Selected costs associated with intimate partner violence were estimated for a community sample of 309 Canadian women who left abusive male partners on average 20 months previously. Total annual estimated costs of selected public- and private-sector expenditures attributable to violence were $13,162.39 per woman. This translates to a national annual cost of $6.9 billion for women aged 19–65 who have left abusive partners; $3.1 billion for those experiencing violence within the past three years. Results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 26 publications
1
44
0
1
Order By: Relevance
“…Use of Safety Actions , measured on a 22 item self-report scale, adapted from several sources, including the Safety Behavior Checklist [48], Intimate Partner Violence Strategies Index [49] and our previous longitudinal research [50]. Women are asked to indicate whether they have used a variety of safety behavior strategies/actions (yes/no) within the past 12 months and, if used, how helpful this strategy was it in dealing with the violence (on a 5-point scale ranging from ‘not at all helpful’ to ‘very helpful’).…”
Section: Methodsmentioning
confidence: 99%
“…Use of Safety Actions , measured on a 22 item self-report scale, adapted from several sources, including the Safety Behavior Checklist [48], Intimate Partner Violence Strategies Index [49] and our previous longitudinal research [50]. Women are asked to indicate whether they have used a variety of safety behavior strategies/actions (yes/no) within the past 12 months and, if used, how helpful this strategy was it in dealing with the violence (on a 5-point scale ranging from ‘not at all helpful’ to ‘very helpful’).…”
Section: Methodsmentioning
confidence: 99%
“…We did not include the already well-reviewed and analyzed public health research on intimate partner violence here because this literature focuses rather more on the impacts of IPV on women than on children. In that regard, we refer readers to the following for a comprehensive overview of the International Journal of Child, Youth and Family Studies (2014) 5(4): 493-587 In Harm's Way: A Special Issue on the Impacts and Costs of Witnessing Intimate Partner Violence public health research on the impacts of IPV: Afifi (2011), Black et al (2008), Public Health Agency of Canada (2010), and Varcoe et al (2011).…”
Section: Literature Review Methodologymentioning
confidence: 99%
“…Leaving an abusive partner may not stop violence (Campbell, Rose, Kub, & Ned, 1998 ; Wuest, Ford-Gilboe, Merritt-Gray, & Berman, 2003 ) or improve health (Anderson, Saunders, Yoshihama, Bybee, & Sullivan, 2003 ). In Canada, we found that women in the early years after leaving had poorer physical and mental health and higher rates of health service use than women in general, with higher annual health system costs by approximately $4,970 Canadian per woman (Ford-Gilboe et al, 2009 ; Varcoe et al, 2011 ; Wuest et al, 2007 2008, 2009, 2010).…”
Section: Health Care Of Women Survivors Of Abusive Relationshipsmentioning
confidence: 99%